The Oblique Extended Reverse First Dorsal Metacarpal Artery Perforator Flap for Coverage of the Radial-Volar Defect of the Proximal Interphalangeal Joint in the Index Finger: A Case Report - Kim, Jeeyoon; Seo, Bommie Florence; Lee, Junho; Jung, Sung No (Archives of Plastic Surgery, 2022)
The dorsal metacarpal artery perforator flap is a flap that rises from the hand dorsum. Owing to its reliability and versatility, this flap is used as a workhorse for finger defect. However, to cover the radial-volar defect of the proximal interphalangeal joint (PIPJ) of the index finger, a longer flap is required than before. Here, we introduce the oblique extended reverse first dorsal metacarpal artery (FDMA) perforator flap to cover the radial-volar aspect defect of the index finger. A 45-year-old man got injured to the radial-volar defect of PIPJ of the left index finger caused by thermal press machine. The wound was 2 × 1 cm in size, and the joint and bone were exposed. We used FDMA perforator from anastomosis with palmar metacarpal artery at metacarpal neck. Since the defect was extended to the volar side, the flap was elevated by oblique extension to the fourth metacarpal base level. The fascia was included to the flap, and the flap was rotated counterclockwise. Finally, PIPJ was fully covered by the flap. Donor site was primarily closed. After 12 months of operation, the flap was stable without complication and limitation of range of motion. The oblique extended reverse FDMA perforator flap is a reliable method for covering the radial-volar defect of the PIPJ of the index finger. This flap, which also has an aesthetic advantage, will be a good choice for hand surgeons who want to cover the PIPJ defect of the index finger using a nonmicrosurgical option.
Keywords: finger injuries; perforator flap; hand injuries